Long noncoding RNA SNHG25 promotes the malignancy of endometrial cancer by sponging microRNA-497-5p and increasing FASN expression - Yuhua He; Shuifang Xu; Yi Qi; Jinfang Tian; Fengying Xu (Journal of Ovarian Research, 2021)
Abstract Background Small nucleolar RNA host gene 25 (SNHG25), a long noncoding RNA, has been well-studied in epithelial ovarian cancer. However, the specific functions of SNHG25 in endometrial cancer (EC) have not been studied yet. In this study, we aimed to elucidate the clinical significance of SNHG25 in EC and determine the regulatory activity of SNHG25 on the tumor-associated EC phenotype. We also thoroughly explored the molecular mechanisms underlying SNHG25 function in EC. Methods Gene expression was measured using quantitative real-time polymerase chain reaction. The detailed functions of SNHG25 in EC were examined by performing loss-of-function experiments. Moreover, the regulatory mechanisms involving SNHG25, microRNA-497-5p, and fatty acid synthase (FASN) were unveiled using the luciferase reporter assay and RNA immunoprecipitation. Results We observed a high level of SNHG25 in EC using the TCGA dataset and our study cohort. Patients with a high SNHG25 level had shorter overall survival than those with a low SNHG25 level. SNHG25 deficiency resulted in tumor-repressing activities in EC cells by decreasing cell proliferation, migration, and invasion and promoting cell apoptosis. Furthermore, the function of SNHG25 depletion in impairing tumor growth in vivo was confirmed. SNHG25 sequestered miR-497-5p as a competing endogenous RNA in EC and consequently positively regulated FASN expression. Thus, the decrease in miR-497-5p or increase in FASN could neutralize the modulatory actions of SNHG25 knockdown in EC cells. Conclusions The depletion of SNHG25 impedes the oncogenicity of EC by targeting the miR-497-5p/FASN axis. The newly elucidated SNHG25/miR-497-5p/FASN pathway may be a promising target for the molecular-targeted management of EC.